UTILIZATION OF AI IN LA TEENAGER'S LIFE: POSTHUMANISM READING IN NICOLAS JOHNSON'S MOVIE MISSING - Sitio, Elizabeth; Mendrofa, Melania Priska (STBA Prayoga Padang, 2024)
AI technology has spread to all social lines, especially those used by teenagers. Inthis research, the researcher analyzes the use of AI by June, the main character in themovie Missing. In this theory, the researcher focuses on transhumanism andsingularity. The researcher used qualitative methods in words, phrases, andsentences. The result showed that the sophistication of AI technology is utilized in aLos Angeles teenager's life, such as digital assistants, on-demand transportation, andproducts and services. In addition, this research also shows that the socialrelationships of teenagers are affected by technology, triggering etiquette changesand negative assumptions from society.